Knowledge Management Strategies and Applications - Mohiuddin, Muhammad; Halilem, Norrin; Ahasanul Kobir, SM; Yuliang, Cao (IntechOpen, 2017)
Knowledge management (KM) has become an important business strategy in an era of accelerated globalization, digitalization, and servitization of products and services. Maximizing the use of organizational resources becomes fundamental for continuous growth and prosperity. Organizations of various kinds such as resource-based organizations, product-based organizations, as well as knowledge-intensive service-oriented organizations require specific policies and support services to improve the knowledge management in their respective organizations. Knowledge Management Strategies and Applications focuses on the way organizations can create knowledge, share existing or new knowledge, and disseminate them among the stakeholders, most importantly among the employees, managers, customers, and suppliers. The selected topics are drawn from several fields of studies and give a multidisciplinary outlook. The book will be interesting not only for the researchers and students but also for the managers who want to improve knowledge sharing and innovation capabilities in their organizations.